2018
DOI: 10.1088/1674-4527/18/6/72
|View full text |Cite
|
Sign up to set email alerts
|

Physical and geometrical parameters of VCBS XIII: HIP 105947

Abstract: The perfect physical and geometrical parameters of the main-sequence close visual binary system (CVBS); HIP 105947, are explicitly presented. These parameters have been constructed conclusively using Al-Wardat's complex method for analysing CVBSs, which is a method for constructing a synthetic spectral energy distribution (SED) for the entire binary system using individual SED for each component star. Which in its turn built using Kurucz (ATLAS9) line-blanketed plane-parallel models. At the same time, the orbi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Atmospheric and fundamental parameters of the components of BMSs have been estimated using Al-Wardat's method Al-Wardat et al (2021a). The method was successfully used to accurately analyze several BMSs (see, e.g., Al-Wardat 2002, 2009a, 2009bAl-Wardat et al 2014a, 2014b, 2016Masda et al 2016;Al-Wardat et al 2017;Masda et al 2018Masda et al , 2019aMasda et al , 2019bAl-Tawalbeh et al 2021;Yousef et al 2021;Al-Wardat et al 2021b). It has been shown to be an effective tool for investigating the accuracy of the measured trigonometric parallaxes by the Hipparcos and Gaia astrometric missions.…”
Section: Methodsmentioning
confidence: 99%
“…Atmospheric and fundamental parameters of the components of BMSs have been estimated using Al-Wardat's method Al-Wardat et al (2021a). The method was successfully used to accurately analyze several BMSs (see, e.g., Al-Wardat 2002, 2009a, 2009bAl-Wardat et al 2014a, 2014b, 2016Masda et al 2016;Al-Wardat et al 2017;Masda et al 2018Masda et al , 2019aMasda et al , 2019bAl-Tawalbeh et al 2021;Yousef et al 2021;Al-Wardat et al 2021b). It has been shown to be an effective tool for investigating the accuracy of the measured trigonometric parallaxes by the Hipparcos and Gaia astrometric missions.…”
Section: Methodsmentioning
confidence: 99%
“…Nordström et al (2004) observed a double-lined RV spectrum for component A, affirming that the star is a subbinary system. The system was also determined as binary by Balega et al (2006), Mason et al (2010), andMasda et al (2018b). The first orbit for HIP 105947 was built by Balega et al (2006), using the Monet (1979) orbital analysis method.…”
Section: Hip 105947mentioning
confidence: 99%
“…Mason et al (2010) modified the orbit of the system using the newly released positional measurements and estimated a mass sum of 2.30 ± 1.14M e . The most recent analyses for HIP 105947 were performed by Masda et al (2018b) and Tokovinin (2019). Masda et al (2018b) estimated the physical parameters of the system as a binary using the method.…”
Section: Hip 105947mentioning
confidence: 99%
See 1 more Smart Citation
“…These make it an ideal technique to study the properties of these systems. A series of papers that determine the complete set of physical and orbital properties of CVBMSs using this method and dynamical modeling technique developed by Tokovinin (1992), respectively, have been published for many systems (e.g., Al-Wardat 2007, Al-Wardat & Widyan 2009, Al-Wardat 2009, Al-Wardat 2012, Al-Wardat et al 2014a, Al-Wardat et al 2014b, Al-Wardat et al 2017, Masda et al 2018, Masda et al 2019band Masda et al 2019a). These analytical papers aim at taking the advantage of CVBMSs in estimating the key properties of the stellar components which is crucial in understanding the formation and evolution of the systems.…”
Section: Introductionmentioning
confidence: 99%